RUNX2 Reverses p53-Induced Chemotherapy Resistance in Gastric Cancer - Huang Y; Liang L; Zhao YX; Yao BH; Zhang RM; Song L; Zhang ZT (Pharmacogenomics and Personalized Medicine, 2023)
Yuan Huang,1 Lu Liang,2 Yong-Xiang Zhao,3 Bi-Hui Yao,2 Rui-Min Zhang,3 Lei Song,2 Zhong-Tao Zhang1 1Department of General Surgery, Beijing Friendship Hospital, Capital Medical University, Beijing, 100050, People’s Republic of China; 2Department of General Surgery, Baotou Central Hospital, Baotou, 014000, People’s Republic of Chin; 3Department of Pediatrics and Urology Surgery, Baotou No.4 Hospital, Baotou, 014000, People’s Republic of ChinaCorrespondence: Zhong-Tao Zhang, Department of General Surgery, Beijing Friendship Hospital, Capital Medical University, No. 95 Yongan Road, Xicheng District, Beijing, 100050, People’s Republic of China, Tel +8613801060364, Email zhangzht@ccmu.edu.cnObjective: Gastric cancer is one of the most common malignancies worldwide; however, its overall mortality has not improved significantly over the last decade. Chemoresistance plays a critical role in this issue. This study aimed to clarify the role and mechanism of runt-related transcription factor 2 (RUNX2) in platinum-based chemotherapy resistance.Methods: First, a drug-resistant model of gastric cancer cells was established to evaluate the relative expression level of the RUNX2 as a potential biomarker of chemotherapy resistance. Next, exogenous silencing was conducted to study whether RUNX2 could reverse drug resistance and understand the underlying mechanisms. Simultaneously, the correlation between the clinical outcomes of 40 patients after chemotherapy and the RUNX2 expression levels in tumor samples was analyzed.Results: We discovered that RUNX2 was significantly expressed in drug-resistant gastric cancer cells and tissues; it was also reversibly resistant to transformation treatment by exogenous RUNX2 silencing. It is confirmed that RUNX2 negatively regulates the apoptosis pathway of the p53 to reduce the chemotherapeutic effects of gastric cancer.Conclusion: RUNX2 is a possible target for platinum-based chemotherapy resistance.Keywords: gastric cancer, RUNX2, platinum, chemotherapy resistance